Patients’ satisfaction survey on healthcare services among non-communicable disease patients at a tertiary care hospital in Puducherry - Rajagopal, Anandaraj; Chellamuthu, Lalithambigai; Dhasaram, Premnath; Kavita Vasudevan; Mathiyalagen, Prakash (Indian Journal of Community Health, 2021)
Background: Patient satisfaction is a scale to assess the services offered by the healthcare system. Patient’s feedback is necessary to identify problems that need to be resolved in improving health services. Aim & Objective: Keeping this in view, the present study is an initiative to estimate the patient’s satisfaction in service provision among NCD patients at a tertiary care hospital of Puducherry. Settings and Design: A Facility-based descriptive cross-sectional study was conducted among NCD patients attending General medicine OPD of a tertiary care hospital of Puducherry between April-June 2019. Methods and Material: Assuming 50% satisfaction level among study participants and 5% non-response rate, the sample size was estimated as 404. The NCD register maintained at the General medicine OPD was considered as the sampling frame & systematic random sampling was applied, so that every 5th patient satisfying the inclusion criteria will be included. A standardized patient satisfaction questionnaire with 31-items (4 domains) which is validated for Indian setting (Cronbach’s alpha 0.96) was used. Statistical analysis used: Data capture was done using Epicollect-5 android application and analysed using SPSS version 16.0. Results: Among the 404 NCD patients, the mean age was 56 ± 11.8 (SD) years and 60.6% were females. One in four patients felt poor in reception, doctor-patient relationship and dispensary services. The overall satisfaction of study subjects categorized as good, satisfactory, poor was 6%, 86% and 8% respectively. Conclusions: Majority of the study participants were satisfied with the service provision of the health facility. Still, there is a scope for improvement in dispensary, doctor-patient relationship and registration services.